Considerations for readdressing theoretical descriptions of particle-reinforced composite food gels. (August 2019) - Gravelle, Andrew J.; Nicholson, Reed A.; Barbut, Shai; Marangoni, Alejandro G.
Abstract: The aim of this work was to address the ability of established theoretical models to describe the small deformation mechanical properties of particle-filled food protein gels. To this end, the effect of incorporating glass microspheres on the elastic modulus of heat-set whey protein isolate/xanthan gum gels is reported. Filler size and polydispersity strongly influenced the observed reinforcement with increasing filler content; however, these effects were also strongly correlated to the ionic strength of the gelator phase (0–200 mM NaCl). Fillers with greater polydispersity provided less reinforcement at high filler content, which was associated with improved packing efficiency. Increasing ionic strength reduced the extent of filler/matrix binding, drastically reducing the impact of the smaller glass microspheres (4 μm, 7–10 μm). Larger particles increased the elastic modulus at high salt content due to interfacial stress concentration and particle-particle contacts. Theoretical fits could not satisfactorily describe the general trend in reinforcement observed with increasing filler content, despite employing various methods to account for the effects of filler self-crowding. Using an empirical approach, we propose an alternative functional form which provides improved fits over the entire range of filler content investigated. This general power law (GPL) model provided physically reasonable values for the maximum packing fraction through an empirically-derived expression for the scaling exponent. A weighted average approach was also proposed to incorporate effects of imperfect filler/matrix adhesion. This method incorporates contributions of both bound and unbound fillers, providing a means to model the effect of increasing ionic strength. Graphical abstract: Unlabelled Image Highlights: Glass microspheres were used as model fillers in whey protein-based composite gels. Established particle reinforcement models did not accurately fit experimental data. An empirical general power law (GPL) model was proposed, providing excellent fits. The GPL model gave reasonable values for the maximum filler packing fraction. The GPL model could be adapted to incorporate imperfect filler/matrix adhesion.